On unified theoretical models, dynamical torsion and spin - Cirilo-Lombardo, Diego Julio (Вопросы атомной науки и техники, 2012)
Unified field theoretical models based on generalized affine geometries are proposed, described and analyzed from the physical and mathematical points of view. The relation between torsion and spin of the models is explicitly shown and some of their physical consequences, as the modification of the anomalous momentum of the elementary particles, are discussed. Модели единой теории поля, основанные на обобщенных аффинных геометриях, предложены, описаны и проанализированы с физико-математической точки зрения. Явно показана связь между кручением и спином в этих моделях. Обсуждаются некоторые их физические следствия, например, модификация аномального импульса элементарных частиц. Моделі єдиної теорії поля, засновані на узагальнених афінних геометріях, запропоновані, описані й проаналізовані з фізико-математичної точки зору. Явно показаний зв'язок між крутінням і спином у цих моделях. Обговорюються деякі їхні фізичні наслідки, наприклад, модифікація аномального імпульсу елементарних часток.